Design and Implementation of Battery Charger with Power Factor Correction using Sepic Converter and Full-bridge DC-DC Converter - Moh. Zaenal Efendi; Novie Ayub Windarko; Moh. Faisal Amir (National Research and Innovation Agency, 2013)
This paper presents a design and implementation of a converter which has a high power factor for battery charger application. The converter is a combination of a SEPIC converter and a full-bridge DC-DC converter connected in two stages of series circuit. The SEPIC converter works in discontinuous conduction mode and it serves as a power factor corrector so that the shape of input current waveform follows the shape of input voltage waveform. The full-bridge DC-DC converter serves as a regulator of output voltage and operates at continuous conduction mode. The experimental results show that the power factor of this converter system can be achieved up to 0.96.